Efavirenz pharmacokinetics during the third trimester of pregnancy and postpartum - Tim R. Cressey (2018)
Background: The impact of pregnancy on efavirenz (EFV) pharmacokinetics is unknown. Methods: International Maternal Pediatric Adolescent AIDS Clinical Trials P1026s is an on-going, prospective, nonblinded study of antiretroviral pharmacokinetics in HIV-infected pregnant women that included a cohort receiving 600 mg EFV once daily as part of combination antiretroviral therapy. Intensive steady-state 24-hour blood sampling was performed during the third trimester and at 6-12 weeks postpartum. Maternal and umbilical cord blood samples were drawn at delivery. Pharmacokinetics targets were the estimated 10th percentile EFV area under the curve (AUC) in nonpregnant historical controls (40.0 mcghr?1mL?1) and a trough concentration of 1 mcg/mL. Results: Twenty-five women were enrolled during the third trimester: median (range) age was 29.3 (18.9-42.9) years, weight 69.0 (40-130) kg, and gestational age 32.9 (30.1-38.7) weeks. Median (range) EFV AUC0-24, Cmax, and C24 hourswere 55.4 mcghr?1mL?1(13.5-220.3), 5.4 mcg/mL (1.9-12.2), and 1.6 mcg/mL (0.23-8.13), respectively. EFV AUC and Cmax did not differ during pregnancy and postpartum but C24 hourswas lower during the third trimester (1.6 vs. 2.1 mcg/mL, P = 0.01). During the third trimester, 5 of 25 (20%) women had an EFV AUC below the target and 3 of 25 (12%) had a trough concentration below 1 mcg/mL. EFV cord blood/maternal concentration ratio was 0.49 (0.37-0.74). All women had a HIV-1 RNA viral load less than 400 copies per milliliter at delivery and 19 (76%) had a viral load below 50 copies per milliliter. One child was perinatally HIV infected. Three women were exposed to EFV throughout the first 6 weeks of pregnancy. EFV was well tolerated, and among the 25 infants, no congenital anomalies or newborn complications were reported. Conclusions: Changes in EFV pharmacokinetics during pregnancy compared with postpartum are not sufficiently large enough to warrant a dose adjustment during pregnancy. Copyright © 2012 by Lippincott Williams & Wilkins.